2016
DOI: 10.1099/ijsem.0.001118
|View full text |Cite
|
Sign up to set email alerts
|

Halostella salina gen. nov., sp. nov., an extremely halophilic archaeon isolated from solar salt

Abstract: Halostella salina gen. nov., sp. nov., an extremely halophilic archaeon isolated from solar salt . In multilocus sequence analysis (MLSA), five housekeeping genes, atpB, EF-2, radA, rpoB¢ and secY, were found to be closely related to those of the members of the genera Halorientalis(89.7 % similarity of the atpB gene sequence), Halomicroarcula(91.9 %, EF-2), Haloterrigena(85.4 %, radA), Natronoarchaeum (89.2 %, rpoB¢) and Natrinema(75.7 %, secY). A phylogenetic tree generated from the results of MLSA of the fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 35 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…It is a well-known property of many halophiles to be polyploid and also to harbor multiple unrelated 16S rRNA gene copies in one cell (Oren, 2012 ). Our previous studies on haloarchaeal taxonomy also revealed that the haloarchaeal taxa such as Halostella salina (Song et al, 2016 ), Halapricum salinum (Song et al, 2014 ), and Halorubrum halophilum (Yim et al, 2014 ), have at least two different copies of the 16S rRNA gene. Because it is accurate to consider all of the reported heterogeneous 16S rRNA gene sequences for the phylogenetic study of the haloarchaea, we used the EzTaxon-e database containing the unrelated 16S rRNA gene copies of the haloarchaea to analyze haloarchaeal community profiles in the commercial salt samples.…”
Section: Discussionmentioning
confidence: 88%
“…It is a well-known property of many halophiles to be polyploid and also to harbor multiple unrelated 16S rRNA gene copies in one cell (Oren, 2012 ). Our previous studies on haloarchaeal taxonomy also revealed that the haloarchaeal taxa such as Halostella salina (Song et al, 2016 ), Halapricum salinum (Song et al, 2014 ), and Halorubrum halophilum (Yim et al, 2014 ), have at least two different copies of the 16S rRNA gene. Because it is accurate to consider all of the reported heterogeneous 16S rRNA gene sequences for the phylogenetic study of the haloarchaea, we used the EzTaxon-e database containing the unrelated 16S rRNA gene copies of the haloarchaea to analyze haloarchaeal community profiles in the commercial salt samples.…”
Section: Discussionmentioning
confidence: 88%
“…Information regarding the community-based genetic and functional traits of archaea in animal habitats is scarce. We have previously reported occurrences of diverse members of extremely halophilic archaea (haloarchaea) in avian plumage [13], as well as in food samples such as salt-fermented seafood [14] and solar salts [15,16]. In the human gut where the microbial entities thrive more abundantly than in other parts of the human body, the archaeome consisted mostly of methane-producing archaea (methanogens), of which, members belonging to the orders Methanobacteriales (including Methanobrevibacter smithii and Methanosphaera stadtmanae) and Methanomassiliicoccales (including Methanomethylophilaceae) are predominant [17].…”
Section: Introductionmentioning
confidence: 99%
“…Information regarding the community-based genetic and functional traits of archaea in animal habitats is scarce. We have previously reported occurrences of diverse members of extremely halophilic archaea (haloarchaea) in avian plumage [13], as well as in food samples such as salt-fermented seafood [14] and solar salts [15,16]. In the human gut where the microbial entities thrive more abundantly than in other parts of the human body, the archaeome consisted mostly of methane-producing archaea (methanogens), of which, members belonging to the orders Methanobacteriales (i.e.…”
Section: Introductionmentioning
confidence: 99%